Pengaruh Harga Paket dan Kualitas Jaringan Internet Terhadap Loyalitas Pelanggan Telkomsel di Wilayah Desa Kaliglagah - Arma Rezaldy; Nur Edi Cahyono; Adi Sucipto (Prospect : Jurnal Manajemen dan Akuntansi, 2024)
The purpose of this study was to examine the effect of package price and network quality on customer loyalty of Telkomsel cards in the Kaliglagah Village area. The sampling technique in this study used a non-probability technique, namely the incidental sampling technique. The population of Telkomsel card users is infinite so that the number of samples in this study was calculated using the Lemeshow formula with the results of 100 respondents. The data analysis techniques used in this study were the Likert scale, validity and reliability tests. Correlation coefficient test, multiple linear regression test, determination analysis, t test, and F test. The results of the multiple linear regression test calculation number Y = 6.105 + 0.411X1 + 0.252X2 showed that every increase in one score for the package price variable is an increase in customer loyalty by 0.411, every increase in one score for the network quality variable will be an increase in customer loyalty by 0.252. The determination test obtained a determination coefficient of 0.559 that the customer loyalty variable can be influenced by the package price and network quality variables by 55.9%. From the t-test, it can be concluded that the package price variable (X1) has a positive and significant effect on the customer loyalty variable because it has a significance of 0.000 (P>0.05) and a calculated t value> t table (4.601> 1.984), meaning that the package price variable (X1) has a positive and significant effect on customer loyalty (Y). The same applies to the network quality variable (X2) which has a significance of 0.000 (P>0.05) and a calculated t value> t table (3.086> 1.984), so it can be concluded that the network quality variable (X2) has a positive and significant effect on consumer loyalty (Y). Customer loyalty can be increased by providing additional facilities on the card in the form of affordable Telkomsel card prices, and maintaining stable network quality.